Climatological correlates of seed size in Amazonian forest trees. (29th May 2015) - Malhado, Ana C.M.; Oliveira‐Neto, Jose A.; Stropp, Juliana; Strona, Giovanni; Dias, Livia C.P.; Pinto, Luciana B.; Ladle, Richard J.; Nakashizuka, Tohru
Abstract Question Do precipitation, temperature and seasonality drive variation in the seed size of Amazonian tree genera? Location Amazonia. Methods We use a combination of global biodiversity information facility (GBIF) records, climatic data from BIOCLIM and seed size categories derived from the literature. Results Tree genera with very small seeds were associated with lower temperatures and higher seasonality, but not with precipitation; the opposite patterns being observed for trees with large seeds. These correlations remained even when the numerically dominant (and ecologically specialized) Fabaceae were removed from the analysis. Conclusions Our findings indicate that Amazonian tree genera with smaller seeds occur more frequently in transitional or seasonal forests, and genera with large seeds are more associated with climatically stable rain forests (warmer and less seasonality). These results are broadly consistent with the 'recruitment hypothesis', which predicts that large seeds have a competitive advantage in closed canopy forest vegetation.